Strategi Pemberdayaan Mustahik Berbasis Zakat Produktif pada BAZNAS Kabupaten Jepara - Ita Noviana; Izza Luthfi Suryani (AHKAM, 2026)
Although productive zakat has been widely examined in the Islamic economics literature, studies that specifically investigate mustahik empowerment strategies by zakat management institutions at the regional level remain limited. This study aims to analyze the productive zakat-based mustahik empowerment strategy implemented by BAZNAS of Jepara Regency. This study used a qualitative approach involving 15 informants, consisting of 9 managers of BAZNAS of Jepara Regency and 6 mustahik recipients of the productive zakat program. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model, which includes data reduction, data display, and conclusion drawing. The results showed that the empowerment strategy of BAZNAS of Jepara Regency was carried out through four main stages, namely beneficiary selection, business capital distribution, business mentoring, and program monitoring and evaluation. The productive zakat program contributed to improving the business capacity and economic independence of most mustahik, although program outcomes showed variation influenced by business management ability and market conditions. The conclusion of this study emphasizes that continuous mentoring and supervision are important factors in increasing the effectiveness of productive zakat programs. These findings contribute to the development of empowerment theory and enrich the literature on productive zakat management in the context of regional zakat institutions. The implications of this study provide input for zakat management institutions in strengthening mentoring systems and designing more sustainable economic empowerment programs.